Monetary Uncertainty and Demand for Money Stability in Nigeria: An Autoregressive Distributed Lag Approach - El-Rasheed, Shehu; Abdullah, Hussin; Dahalan, Jauhari (International Journal of Economics and Financial Issues, 2017)
This paper investigates the effect of monetary uncertainty on the stability of money demand function in Nigeria using the ARDL approach for the period of 1980 to 2014. The demand for money in Nigeria is specified as a function of income, domestic interest rate, inflation, nominal exchange rate and monetary uncertainty. The effect of monetary uncertainty on money demand function has not been previously studied in the demand for money literature in Nigeria. The results from the bound testing indicate that monetary uncertainty, income, domestic interest rate, inflation, exchange rate and broad money (M2) are co-integrated. The finding shows that monetary uncertainty has a significant influence on the demand for money function in Nigeria. Evidence has shown a unidirectional causality running from monetary uncertainty to money demand without feedback. The CUSSUM and CUSSUMSQ stability test established that the broad money demand function in Nigeria is stable over the period under study. By implication the monetary policies aimed at monetary targeting could be very effective even when there is the presence of significant monetary uncertainty. Keywords: ARDL, co-integration, money demand, uncertainty, Nigeria. JEL Classifications: E41, E6